High strength, highly formable titanium alloy using molybdenum and ferrochromium and its manufacturing method
A titanium alloy with Molybdenum, Chromium, Iron, and Silicon, produced using ferrochrome, addresses the limitations of existing alloys by achieving high strength and moldability at reduced costs, suitable for aerospace, defense, and medical applications.
Patent Information
- Application Number
- JP2024539777
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-29
- Filing Date
- 2022-12-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-06
AI Technical Summary
Existing titanium alloys, such as Ti-6AL-4V and Ti-ZR, face limitations in strength, elasticity, and cost, making them unsuitable for applications requiring high strength and biological compatibility, particularly in medical implants and glasses frames, due to the high cost of expensive metal raw elements.
A titanium alloy composition comprising Molybdenum (1.0 to 15.0%), Chromium (0.1 to 3.0%), Iron (0.1 to 1.0%), Silicon (0.01 to 0.1%), and Oxygen (0.4% or less), with a β-transformation point of 670 to 815 °C, produced through a method involving the addition of low-cost ferrochrome, which includes stages of mixing, cooling, and heating, to achieve high strength and moldability.
The alloy achieves high tensile strength of 750 to 1510 MPa, improved moldability, and reduced production costs by using low-cost ferrochrome, while maintaining excellent biological compatibility and avoiding toxic elements, thus expanding its application in aerospace, defense, and medical fields.
Smart Images

Figure 2025502827000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to titanium and a manufacturing method thereof, and more particularly to a titanium alloy having high strength and high formability by using molybdenum and ferrochromium, and a manufacturing method thereof. [Background technology]
[0002] Titanium and its alloys are widely used in a wide range of industrial fields, such as aerospace, defense, energy industry, medical care, and consumer goods, due to their high strength, high corrosion resistance, and high biocompatibility.
[0003] Titanium alloys are generally classified into pure titanium, α alloys, α-β alloys, and β alloys based on their stability at room temperature. Among these, α alloys are known to have excellent creep strength and weldability, while β alloys are known to have improved workability.
[0004] Up until now, titanium alloys have mainly been used in industrial applications, such as pure titanium, and Ti-6Al-4V alloy, an α-β alloy for aviation and defense. In medical and consumer goods, Ti-Zr, Ti-Nb, and Ti-Mo alloys, which offer low elastic modulus and high strength, have been used, and research is ongoing to improve their low elastic modulus and high strength. However, due to the limitations of the properties of these alloys, their use has not expanded.
[0005] Pure titanium is cheaper than other titanium alloys in terms of cost, and has excellent formability, weldability, workability, and corrosion resistance, but has low strength and is limited in its application fields, while α-β titanium alloy Ti-6Al-4V has high strength but is expensive and tends to have poorer properties than pure titanium except strength. In addition, β alloys can realize desired properties by controlling the elements added to the alloy, but have the disadvantage of being considerably more expensive than pure titanium and Ti-6Al-4V alloys. In particular, medical implants and eyeglass frames require excellent biocompatibility, low elastic modulus, and high strength properties, and in this case, in order to express all of these properties at the same time, it is necessary to add a large amount of expensive metal elements such as Nb and Ta to titanium.
[0006] Therefore, there is a need to develop titanium alloys made from relatively inexpensive elements that can control properties such as excellent strength, formability, weldability, processability, corrosion resistance, biocompatibility, and low elastic modulus while minimizing cost increases, and methods for manufacturing such alloys. Summary of the Invention [Problem to be solved by the invention]
[0007] The problem to be solved by the present invention is to provide a high-strength, highly formable titanium alloy using molybdenum and ferrochromium.
[0008] In addition, the problem to be solved by the present invention is to provide a method for producing a high-strength, highly formable titanium alloy using ferrochromium as an alloy additive, which not only reduces the production cost of the titanium alloy but also has the advantage of ensuring strength and elongation.
[0009] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned above can be understood from the following description and can be more clearly understood from the embodiments of the present invention. In addition, it can be easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]
[0010] In order to solve the above problems, a titanium alloy according to an embodiment of the present invention is characterized by containing 1.0 to 15.0 weight percent molybdenum (Mo), 0.1 to 3.0 weight percent chromium (Cr), 0.1 to 1.0 weight percent iron (Fe), 0.01 to 0.1 weight percent silicon (Si), 0.4 weight percent or less oxygen (O), with the balance being titanium (Ti) and unavoidable impurities.
[0011] A titanium alloy according to a preferred embodiment of the present invention contains 1.0-15.0 wt% molybdenum (Mo), 0.1-1.98 wt% chromium (Cr), 0.1-0.93 wt% iron (Fe), 0.01-0.09 wt% silicon (Si), and 0.4 wt% or less oxygen (O), with the chromium (Cr) content being greater than the iron (Fe) content, with the remainder being titanium (Ti) and unavoidable impurities, and is characterized by having a tensile strength of 1109-1510 MPa.
[0012] The chromium content may be 1.7 to 4 times the iron content.
[0013] The titanium alloy may have a molybdenum equivalent ([Mo]eq.) of 5.5 to 20, as represented by the following formula 1, and a β transformation point of 670 to 815° C. ([] in formula 1 represents the weight % of the component).
[0014] [Formula 1] [Mo]eq.=[Mo]+0.2[Ta]+0.28[Nb]+0.4[W]+0.67[V]+1.25[Cr]+1.25[Ni]+1.7[Mn]+1.7[Co]+2.5[Fe]
[0015] The titanium alloy may have a tensile strength of 750 to 1510 MPa, a yield strength of 545 to 1420 MPa, and a Young's modulus of 80 to 110 GPa.
[0016] In order to solve the above problems, a method for manufacturing a titanium alloy according to an embodiment of the present invention includes the steps of: (a) adding ferrochrome containing chromium (Cr), iron (Fe), silicon (Si), and carbon (C) to an alloy or mixture of titanium (Ti) and molybdenum; (b) melting the result of step (a) and cooling it to form a titanium alloy base material; and (c) hot forming the titanium alloy base material, wherein the molybdenum is added in an amount of 1 to 15 wt % and the ferrochrome is added in an amount of less than 4 wt % based on the total weight of the titanium alloy.
[0017] A method for producing a titanium alloy according to a preferred embodiment of the present invention includes the steps of: (a) adding ferrochrome containing chromium (Cr), iron (Fe), silicon (Si), and carbon (C) to an alloy or mixture of titanium (Ti) and molybdenum; (b) melting the result of step (a) and cooling it to form a titanium alloy base material; and (c) hot forming the titanium alloy base material, wherein the ferrochrome contains 20-35 wt% iron (Fe), 1-4 wt% silicon (Si), and 0.15 wt% or less carbon (C), with the remainder being chromium (Cr) and unavoidable impurities, and the molybdenum is added in an amount of 1-15 wt% and the ferrochrome is added in an amount of less than 4 wt% based on the total weight of the titanium alloy. In this case, the titanium alloy produced may contain 1.0 to 15.0 weight % molybdenum (Mo), 0.1 to 1.98 weight % chromium (Cr), 0.1 to 0.93 weight % iron (Fe), 0.01 to 0.09 weight % silicon (Si), and 0.4 weight % or less of oxygen (O), with the remainder being titanium (Ti) and unavoidable impurities, and may have a tensile strength of 1109 to 1510 MPa.
[0018] It is more preferable that the ferrochromium be added in an amount of 0.5 to 2% by weight based on the total weight of the titanium alloy.
[0019] The titanium alloy may contain 0.4% by weight or less of oxygen (O) based on the total weight of the titanium alloy.
[0020] The ferrochrome may contain 20 to 35 weight % iron (Fe), 1 to 4 weight % silicon (Si), and 0.15 weight % or less carbon (C), with the remainder being chromium (Cr) and unavoidable impurities.
[0021] The hot forming can be carried out at 800 to 850° C. with a forming rate of up to 90%. Effect of the Invention
[0022] According to the manufacturing method of the high strength and high formability titanium alloy of the present invention, low-carbon ferrochrome made of elements (Cr, Fe, Si, etc.) that are harmless to the human body is used as an additive to titanium-molybdenum alloy material, which can reduce costs in terms of raw material costs and process costs compared to adding individual elements such as Cr, Fe, Si, etc.
[0023] In addition, the high strength and high formability titanium alloy according to the present invention can provide excellent formability as well as excellent strength by controlling the content of ferrochromium.
[0024] The above-mentioned effects and specific effects of the present invention will be described in conjunction with the following description of the preferred embodiment of the invention. [Brief description of the drawings]
[0025] [Figure 1a] FIG. 1 is a diagram showing the phase fraction of a specimen in which 5 wt. % of molybdenum is added to titanium. [Figure 1b] FIG. 1 is a diagram showing the phase fraction of a specimen in which 5 wt. % of molybdenum and 4.0 wt. % of ferrochromium are added to titanium. [Figure 1c] FIG. 1 is a diagram showing the phase fraction of a specimen in which 5 wt. % of molybdenum and 0.5 wt. % of ferrochromium are added to titanium. [Figure 2a]FIG. 1 is a diagram showing the phase fraction of a specimen in which 9.5 wt % of molybdenum is added to titanium. [Figure 2b] FIG. 1 is a diagram showing the phase fraction of a specimen in which 9.5% by weight of molybdenum and 4.0% by weight of ferrochromium are added to titanium. [Figure 2c] FIG. 1 is a diagram showing the phase fraction of a specimen in which 9.5% by weight of molybdenum and 0.5% by weight of ferrochromium are added to titanium. [Figure 3a] FIG. 1 is a diagram showing the phase fraction of a specimen in which 15 wt % of molybdenum is added to titanium. [Figure 3b] FIG. 1 is a diagram showing the phase fraction of a specimen in which 15 wt. % of molybdenum and 4.0 wt. % of ferrochromium are added to titanium. [Figure 3c] FIG. 1 is a diagram showing the phase fraction of a specimen in which 15% by weight of molybdenum and 0.5% by weight of ferrochromium are added to titanium. [Figure 4a] FIG. 1 is a diagram showing mechanical properties of specimens 1 and 4 of comparative examples and specimens 1 to 4 of examples. [Figure 4b] FIG. 1 is a diagram showing mechanical properties of specimens 2 and 5 of comparative examples and specimens 5 to 8 of examples. [Figure 4c] FIG. 1 is a diagram showing mechanical properties of specimens 3 and 6 of comparative examples and specimens 9 to 12 of examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The above-mentioned objects, features and advantages will be described in detail below, so that those skilled in the art can easily implement the technical idea of the present invention. In describing the present invention, if a detailed description of the known technology according to the present invention is considered to make the gist of the present invention unclear, the detailed description will be omitted. Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings.
[0027] Hereinafter, a high-strength, highly formable titanium alloy using molybdenum and ferrochromium according to several embodiments of the present invention and a method for manufacturing the same will be described.
[0028] There are two methods to increase the strength of pure titanium: adding alloy elements to increase the strength, and reducing the size of the internal crystal grains through plastic processing and heat treatment to increase the strength. However, these methods require the addition of an additional process to refine the crystal grains by adding alloy elements, which increases the cost. In addition, the method of refining the crystal grains through plastic processing and heat treatment has the disadvantage that the mechanical properties of the titanium alloy produced depending on the process change significantly, which may lead to a process that is difficult to directly apply to the actual production process.
[0029] Therefore, it can be said that the method of adding alloying elements is more advantageous than the method of refining crystal grains by plastic processing and heat treatment. In particular, it can be said that the most preferable method is to select and alloy inexpensive alloying elements in order to minimize cost increases and increase strength. Furthermore, in order to ensure biostability, it is preferable not to add toxic elements such as Co, Cu, Ni, and V, and the titanium alloy according to the present invention does not contain these elements, although they may be unavoidably contained as impurities in exceptional cases.
[0030] As a result of long research, the inventors selected Mo, which is inexpensive and non-toxic, from among elements (Mo, V, Nb, etc.) that form a complete solid solution (a system that shows complete solubility in both liquid and solid phases) with titanium, and selected Ti-Mo alloy as the base. Fe and Cr were selected as alloying elements that have a greater effect on Mo equivalent (Mo equivalent greater than 1) than Mo, are relatively inexpensive and non-toxic. In addition, in order to overcome the disadvantage that it is difficult to obtain a uniform composition due to volatilization during melting when alloying elements such as Fe and Cr are added individually, a method of alloying by adding ferrochrome containing Fe, Cr, Si, etc. has been developed. In particular, in the case of Si, an element contained in ferrochrome, it is expected to provide a nucleation site during melting and further refine the crystal grains of the melted ingot. As a result, the inventors developed a new Ti-Mo-Cr-Fe-Si alloy based on a titanium-molybdenum (Ti-Mo) alloy.
[0031] The manufacturing method of the high-strength titanium alloy using molybdenum and ferrochromium will be described in more detail below.
[0032] The method for producing a high-strength titanium alloy according to the present invention includes the steps of adding ferrochrome, which includes chromium (Cr), iron (Fe), silicon (Si), and carbon (C), to an alloy or mixture of titanium (Ti) and molybdenum (Mo), melting the titanium and ferrochrome and then cooling to form a titanium alloy base material, and hot forming the titanium alloy base material.
[0033] The melting of titanium, molybdenum and ferrochrome can be performed by various known methods such as vacuum melting, electron beam melting, plasma arc melting, non-consumable electrode arc melting, or induction skull melting. The hot forming can be performed by hot rolling, hot forging, etc. The hot forming can be performed at 800-850°C with a forming ratio of 90% or less. In the case of rolling, the forming ratio can be expressed as a reduction ratio. In the case of the present invention, as described below, 1-15 wt% of molybdenum and less than 4 wt% of ferrochrome are added, and as a result, it is possible to provide an effect of preventing cracks from occurring even when forming at 800-850°C with a forming ratio of 90%.
[0034] After hot forming, various methods can be used for cooling, such as water cooling, air cooling, furnace cooling, etc. The cooling method can be determined depending on whether there is a further hot process after hot forming, for example, if there is no further hot process, water cooling can be performed after hot forming. After hot forming, further heat treatments such as homogenization treatment, solution treatment, aging treatment, etc. can be performed.
[0035] One feature of ferrochrome melting is that the temperature required to melt ferrochrome is significantly lower than the temperature required to melt chromium, iron, silicon, etc. individually, and is similar to the melting point of titanium. This allows ferrochrome to be melted together with titanium at a relatively low temperature, thereby reducing the manufacturing cost of titanium alloys.
[0036] In the present invention, the amount of ferrochromium added is preferably less than 4% by weight based on the total weight of the titanium alloy. More preferably, it is 3% by weight or less, and most preferably, it is 0.5 to 2% by weight. When ferrochromium is added, the strength can be increased compared to a titanium alloy without ferrochromium added. However, when the amount of ferrochromium added is 4% by weight or more, the elongation rate is very low and cracks may occur.
[0037] Ferrochrome may contain 20 to 35 weight percent iron (Fe), 1 to 4 weight percent silicon (Si), and 0.15 weight percent or less carbon (C), with the remainder being chromium (Cr) and unavoidable impurities. Ferrochrome is characterized in that the Cr content is higher than the Fe content. The Cr content in ferrochrome may be 1.7 to 4 times, for example, 2 to 4 times, the Fe content.
[0038] When the content of ferrochromium is less than 4% by weight, the above-mentioned preferred ranges of the contents of chromium, iron, and silicon in the titanium alloy can be satisfied.
[0039] By the above-mentioned method, the present invention can provide a titanium alloy characterized by containing 1.0-15.0% by weight of molybdenum (Mo), 0.1-3.0% by weight of chromium (Cr), 0.1-1.0% by weight of iron (Fe), 0.01-0.1% by weight of silicon (Si), 0.4% by weight or less of oxygen (O), and the balance being titanium (Ti) and inevitable impurities. More preferably, the present invention can provide a titanium alloy characterized by containing 1.0-15.0% by weight of molybdenum (Mo), 0.1-1.98% by weight of chromium (Cr), 0.1-0.93% by weight of iron (Fe), 0.01-0.09% by weight of silicon (Si), and 0.4% by weight or less of oxygen (O), but the chromium (Cr) content is greater than the iron (Fe) content, and the balance being titanium (Ti) and inevitable impurities.
[0040] Molybdenum (Mo) is a non-toxic β-phase stabilizing element. Molybdenum increases strength through its solid solution strengthening effect. However, if too much molybdenum is added in an amount exceeding 15 wt%, it can cause a problem of significantly increasing the elastic modulus of the alloy.
[0041] Chromium (Cr) is a non-toxic element and a beta-phase stabilizing element that is more effective than molybdenum (Mo) in titanium alloys. Adding chromium to titanium can increase strength due to the solid solution strengthening effect. For these effects, chromium must be added in an amount of 0.1% by weight or more. However, if chromium is added in excess of 3.0% by weight, there is a high possibility of fracture during the forming process due to the formation of the Laves Phase (TiCr2). Therefore, the chromium content is preferably 3.0% by weight or less, and more preferably 1.98% by weight or less.
[0042] Iron (Fe), like chromium (Cr), is non-toxic and is a beta-phase stabilizing element with a higher degree of stability than molybdenum. Adding iron to titanium can increase its strength due to the solid solution strengthening effect. For these effects, iron must be added in an amount of 0.1% by weight or more. However, when titanium alloys containing more than 1.0% by weight of iron are melted, macro- or micro-segregation can be induced, and when heat-treated at a certain temperature, a very weak phase, TiFe phase, can be formed. Therefore, the iron content is preferably 1.0% by weight or less, and more preferably 0.9% by weight or less.
[0043] Silicon (Si) is a non-toxic element that forms many nucleation sites when titanium alloys are melted, inducing the refinement of crystal grains. Silicon also contributes to increasing the static strength of titanium alloys. To achieve this effect, silicon must be added in an amount of 0.01% by weight or more. However, if the silicon content exceeds 0.1% by weight, it may promote the generation of cracks due to the formation of brittle silicide. Therefore, the silicon content is preferably 0.1% by weight or less, and more preferably 0.09% by weight or less.
[0044] The contents of Cr, Fe, and Si in the titanium alloy according to the present invention are determined by the amount of ferrochromium added, and the amount of ferrochromium added is less than 4 wt%, more preferably 3.0 wt% or less, and most preferably 0.5 to 2.0 wt%, so that the above-mentioned contents of Cr, Fe, and Si can be satisfied.
[0045] The titanium alloy according to the present invention may contain oxygen (O) in an amount of 0.4% by weight or less based on the total weight of the titanium alloy. Oxygen is an interstitial element that does not significantly affect corrosion resistance and is a solid-solution strengthening alloying element that strengthens the lattice. However, if the oxygen content exceeds 0.4% by weight, twin deformation at low temperatures is suppressed, which can lead to a rapid decrease in impact resistance.
[0046] As will be understood from the examples described later, the titanium alloy according to the present invention may have a molybdenum equivalent ([Mo]eq.) represented by the following formula 1 of 5.5 to 20 ([] in formula 1 is the weight % of the component).
[0047] [Formula 1] [Mo]eq.=[Mo]+0.2[Ta]+0.28[Nb]+0.4[W]+0.67[V]+1.25[Cr]+1.25[Ni]+1.7[Mn]+1.7[Co]+2.5[Fe]
[0048] The high-strength titanium alloy according to the present invention may have a β transformation point of 670 to 815°C.
[0049] Furthermore, experimental results show that the high-strength titanium alloy according to the present invention may have a tensile strength of 750 to 1510 MPa, and more preferably a tensile strength of 1109 to 1510 MPa, a yield strength of 545 to 1420 MPa, and a Young's modulus of 80 to 110 GPa, taking into account the elongation rate according to the following examples.
[0050] Working Example Hereinafter, the configuration and function of the present invention will be described in more detail with reference to preferred examples of the present invention. However, these are merely preferred examples of the present invention, and are not to be construed as limiting the present invention in any sense. Contents not described in the following examples can be fully inferred by those skilled in the art, and therefore the description thereof will be omitted.
[0051] 1. Analysis of Ferrochrome The three ferrochrome specimens were subjected to component analysis as follows. EDS analysis was performed three times for each of the three locations (left, center, and right) of each 10 mm x 10 mm specimen. The results are shown in Table 1.
[0052] [Table 1]
[0053] All three specimens contained about 66% by weight of Cr, about 31% by weight of Fe, and about 3% by weight of Si, and it was found that the difference in the content of the components was not large.
[0054] In the following, an experiment was carried out on ferrochrome specimen #1.
[0055] After removing the surface oxide layer from ferrochrome specimen #1, the contents of O, N, H, and C were analyzed by EDS. The results are shown in Table 2.
[0056] [Table 2]
[0057] Ferrochrome is classified into low carbon ferrochrome, medium carbon ferrochrome, and high carbon ferrochrome according to the carbon content, and among these, low carbon ferrochrome means that the carbon content is 0.2 weight % or less or 0.15 weight % or less. In the case of the ferrochrome specimen #1 analyzed above, the carbon content is about 0.1 weight % and the chromium content is about 67%, which corresponds to low carbon ferrochrome.
[0058] The melting points of Cr, Fe and Si are 1907°C, 1538°C and 1414°C, respectively, but it is known that the melting point of low-carbon ferrochrome, which has a carbon content of 0.15% by weight or less, is about 1620°C. In addition, the melting point of titanium is 1668°C.
[0059] O, N, C, H, etc. in titanium are the main elements that reduce fracture ductility and require special management. These elements in pure titanium must be controlled to the weight percent or less shown in Table 3 (there are very small differences in the allowable values depending on the country). H in particular requires special management compared to other elements because even a small amount of it reduces fracture ductility.
[0060] [Table 3]
[0061] In the case of the ferrochrome specimen #1 analyzed above, it is a low carbon ferrochrome and satisfies the maximum weight percent or less for elements such as O, N, C, and H in Table 3.
[0062] Titanium alloy specimen manufacturing Titanium (Ti-0.02O) and molybdenum and ferrochromium in the amounts shown in Table 4 were melted in an induction skull melting furnace to form a titanium alloy, which was then cooled to produce an ingot measuring 10 mm wide x 30 mm long x 10 mm thick.
[0063] The ingots were formed at 830° C.±20° C. with a forming ratio of about 90% as shown in Table 4, and then water-cooled to prepare titanium alloy specimens according to Comparative Examples 1-3 and Examples 1-12.
[0064] Table 4 shows the Mo equivalent and β transformation point according to the content of ferrochromium in the titanium alloy specimens manufactured according to Comparative Examples 1 to 3 and Examples 1 to 12. And Table 5 shows the contents of Cr, Fe and Si in the titanium alloy specimens according to Examples 1 to 12, which are added with ferrochromium.
[0065] [Table 4]
[0066] [Table 5] ※Cr:Fe:Si=66:31:3
[0067] Figure 1a shows the phase fraction of a titanium specimen with 5 wt% molybdenum added. Figure 1b shows the phase fraction of a titanium specimen with 5 wt% molybdenum and 4.0 wt% ferrochromium added. Figure 1c shows the phase fraction of a titanium specimen with 5 wt% molybdenum and 0.5 wt% ferrochromium added.
[0068] 1a to 1c, the specimen with 5 wt% molybdenum added to titanium and the specimen with 5 wt% molybdenum and 0.5 wt% ferrochromium added to titanium show almost no TiCr2 precipitate phase, whereas the specimen with 5 wt% molybdenum and 4.0 wt% ferrochromium added to titanium shows about 5.63 wt% TiCr2 precipitate phase. As mentioned above, if there is too much TiCr2, there is a possibility of fracture during the forming process, so it is necessary to add less than 4.0 wt%, more preferably 3.0 wt% or less, and even more preferably 0.5 to 2.0 wt% ferrochromium.
[0069] Figure 2a shows the phase fractions of a titanium specimen with 9.5 wt% molybdenum added, Figure 2b shows the phase fractions of a titanium specimen with 9.5 wt% molybdenum and 4.0 wt% ferrochromium added, and Figure 2c shows the phase fractions of a titanium specimen with 9.5 wt% molybdenum and 0.5 wt% ferrochromium added.
[0070] 2a to 2c, the specimen with 9.5 wt% molybdenum added to titanium and the specimen with 9.5 wt% molybdenum and 0.5 wt% ferrochromium added to titanium showed almost no TiCr2 precipitate phase, whereas the specimen with 9.5 wt% molybdenum and 4.0 wt% ferrochromium added to titanium showed about 5.63 wt% TiCr2 precipitate phase.
[0071] Figure 3a shows the phase fractions of a titanium specimen with 15 wt% molybdenum added, Figure 3b shows the phase fractions of a titanium specimen with 15 wt% molybdenum and 4.0 wt% ferrochromium added, and Figure 3c shows the phase fractions of a titanium specimen with 15 wt% molybdenum and 0.5 wt% ferrochromium added.
[0072] 3a to 3c, the specimen with 15 wt% molybdenum added to titanium and the specimen with 15 wt% molybdenum and 0.5 wt% ferrochromium added to titanium showed almost no TiCr2 precipitate phase, whereas the specimen with 15 wt% molybdenum and 4.0 wt% ferrochromium added to titanium showed about 5.63 wt% TiCr2 precipitate phase.
[0073] Figures 4a to 4c show the mechanical properties of Comparative Examples 1 to 6 and Examples 1 to 12. Specifically, Figure 4a shows the mechanical properties of Comparative Examples 1 and 4 and Examples 1 to 4, which have a molybdenum content of 5.0 wt%, Figure 4b shows the mechanical properties of Comparative Examples 2 and 5 and Examples 5 to 8, which have a molybdenum content of 9.5 wt%, and Figure 4c shows the mechanical properties of Comparative Examples 3 and 6 and Examples 9 to 12, which have a molybdenum content of 15 wt%.
[0074] The specimen according to Comparative Example 4 is a titanium alloy specimen manufactured by adding 5.0 wt% molybdenum and 4 wt% ferrochromium, the specimen according to Comparative Example 5 is a titanium alloy specimen manufactured by adding 9.5 wt% molybdenum and 4 wt% ferrochromium, and the specimen according to Comparative Example 5 is a titanium alloy specimen manufactured by adding 15 wt% molybdenum and 4 wt% ferrochromium.
[0075] The mechanical properties were obtained by carrying out tensile tests on each titanium alloy specimen at room temperature and at a deformation rate of 1.5 mm / min.
[0076] Table 6 shows the mechanical properties of the comparative samples 1 to 3 and the example samples 1 to 12.
[0077] [Table 6]
[0078] Referring to Table 6, it can be seen that the titanium-molybdenum alloy specimens according to Comparative Examples 1 to 3, which do not contain ferrochromium, exhibit tensile strengths of 786 to 1064 MPa and yield strengths of 712 to 855 MPa. In contrast, it can be seen that the titanium alloy specimens manufactured by adding 3.0 wt% or less of ferrochromium to the titanium-molybdenum alloy exhibit a maximum tensile strength of 1510 MPa and a maximum yield strength of 1420 MPa. In other words, it can be seen that the strength of the titanium alloy manufactured by adding ferrochromium is increased compared to the titanium alloys without ferrochromium.
[0079] In particular, referring to Table 6, it can be seen that in the cases of Examples 2 to 4, the tensile strength is 1109 to 1510 MPa and the elongation ratio is good.
[0080] Table 7 shows the measurement results of the elongation ratios of the specimens according to Comparative Examples 4 to 6 and the specimens according to Examples 1 to 12 and the observation results of crack occurrence.
[0081] [Table 7]
[0082] 4a to 4c and Table 7, in the case of Comparative Examples 4 to 6, when 4.0 wt% ferrochromium was added to the titanium alloy in which 5 to 15 wt% molybdenum was added to titanium, the elongation rate was rapidly decreased to 1.4 to 2.3%. In contrast, in the case of Examples 1 to 12, when less than 4.0 wt% ferrochromium was added to the titanium alloy in which 5 to 15 wt% molybdenum was added to titanium, the elongation rate did not rapidly decrease and the range of elongation rate was expressed as 2.4 to 49%. Furthermore, when the amount of ferrochromium added was 0.5 to 2.0 wt%, an even higher elongation rate was shown, and considering both the strength and the elongation rate, it can be said that the amount of ferrochromium added is most preferably 0.5 to 2.0 wt%.
[0083] Also, referring to Table 7, it can be seen that cracks were generated in the titanium alloy specimens according to Comparative Examples 4 and 6, but no cracks were generated in the titanium alloy specimens according to Examples 1 to 12.
[0084] Although the present invention has been described above with reference to the illustrative drawings, the present invention is not limited to the embodiments and drawings disclosed in this specification, and it is clear that various modifications can be made by those skilled in the art within the scope of the technical concept of the present invention. Furthermore, even if the effects of the configuration of the present invention are not explicitly described and explained while the embodiments of the present invention are described above, it is natural that the effects that can be predicted by the configuration should also be recognized.
Claims
1. The alloy contains 1.0 to 15.0 weight percent molybdenum (Mo), 0.1 to 1.98 weight percent chromium (Cr), 0.1 to 0.93 weight percent iron (Fe), 0.01 to 0.09 weight percent silicon (Si), and 0.4 weight percent or less oxygen (O), but the chromium (Cr) content is greater than the iron (Fe) content, with the remainder being titanium (Ti) and unavoidable impurities; Characterized in that it has a tensile strength of 1109 to 1510 MPa. Titanium alloy.
2. The chromium content is 1.7 to 4 times the iron content.
2. The titanium alloy of claim 1.
3. The titanium alloy is characterized in that it has a molybdenum equivalent ([Mo]eq.) represented by the following formula 1 of 5.5 to 20 and a β transformation point of 670 to 815 ° C.
2. The titanium alloy of claim 1. [Formula 1] [Mo]eq. = [Mo] + 0.2 [Ta] + 0.28 [Nb] + 0.4 [W] + 0.67 [V] + 1.25 [Cr] + 1.25 [Ni] + 1.7 [Mn] + 1.7 [Co] + 2.5 [Fe]
4. The titanium alloy has a yield strength of 545 to 1420 MPa and a Young's modulus of 80 to 110 GPa.
2. The titanium alloy of claim 1.
5. (a) adding ferrochrome, which includes chromium (Cr), iron (Fe), silicon (Si), and carbon (C), to an alloy or mixture of titanium (Ti) and molybdenum; (b) forming a titanium alloy base material by melting and cooling the resultant of step (a); (c) hot forming the titanium alloy base material; Including, The ferrochrome contains 20 to 35% by weight of iron (Fe), 1 to 4% by weight of silicon (Si), and 0.15% by weight or less of carbon (C), with the remainder being chromium (Cr) and unavoidable impurities; The titanium alloy is characterized in that 1 to 15% by weight of the molybdenum and less than 4% by weight of the ferrochromium are added relative to the total weight of the titanium alloy. A method for manufacturing titanium alloys.
6. The ferrochromium is added in an amount of 0.5 to 2% by weight based on the total weight of the titanium alloy. A method for producing the titanium alloy according to claim 5.
7. The hot forming is performed at 800 to 850 ° C. with a forming rate of 90% or less. A method for producing the titanium alloy according to claim 5.
8. The titanium alloy produced contains 1.0 to 15.0 wt% molybdenum (Mo), 0.1 to 1.98 wt% chromium (Cr), 0.1 to 0.93 wt% iron (Fe), 0.01 to 0.09 wt% silicon (Si), 0.4 wt% or less oxygen (O), the balance being titanium (Ti) and unavoidable impurities, and has a tensile strength of 1109 to 1510 MPa. A method for producing the titanium alloy according to claim 5.
Citation Information
Patent Citations
Low-cost titanium alloy and preparation method thereof
CN103045905A
Heat resistant titanium alloy sheet excellent in cold workability and process for producing the same
JP2005298970A
Titanium alloy excellent in strength and ductility at room temperature
JP2012052178A
A method for improving the mechanical strength of a titano alloy having an α'' phase by cold working.
JP2015507689A
Beta-type titanium alloy having low elastic modulus and high strength
US20150147225A1